Estimation of Software Reliability Using p – TEF Models - Saxena, Suneet; Gupta, Ajay (International Journal of Computer Sciences and Engineering, 2025)
The paper present NHPP Software Reliability Growth model involving test effort function(TEF) and fault removal efficiency(TEF). TEF deals with the problem of limited time and resources available during software testing phase. FRE addresses the problem of multiple occurrences of fault before its final removal. In this paper we propose p-TEF models which incorporate both TEF and FRE. p is FRE which represent fraction of faults detected and corrected. If p is less than one, then debugging is imperfect whereas for p equals to one debugging is perfect. Existing TEF models compared with p-TEF models using statistical tools SSE , R2 and AIC. Results suggest that the p-TEF models fits and predict faults detection data better.